Control+c: autoria na rede - Costa, Maria Teresa Tavares (2007)
Ctrl+C Authorship on the Net studies the new formats of creation that emerged from the Internet. By aiming beyond the discussions around a legal point of view, this work focusses on asthetic and critical parameters of online art experiences, which point towards the redefinition of the concept of authorship in the realm of digital media e the very context of contemporary culture. In order to cruise this itinerary, the text starts from an understanding of the technical particularities of the network, related to the symbolic exchanges established in its environment. In a first phase, the research investigates the concept of Network Culture through the social-technical relations which are its components. On the discussion proposed by Alexander Galloway concerning the protocols that rule the communication flux on the Internet, the concepts of code and interface are articulated, aiming to define a language digital objects. The theories of Lev Manovich, Margot Lovejoy, Florian Cramer and Jay David Bolter & Richard Grusin are utilized in order to further develop these discussions. After defining the specifities of the Network Culture, it became possible, in a second instance, to analyze de development of what Lawrence Lessig denominates as Remix Culture, in other words, a social configuration marked by semiotic appropriation and recontextualization typical of those new digital technologies. About Lessig s concept are discussed the aesthetic parameters of the remix cultures on the terrain of network culture through Eduardo Nava s analysis in parallel with the concepts of modularity and remixability by Lev Manovich, digital aura in Michael Betancourt and remix as consumption from Nicolas Bourriard. From the methodological perspective, a mapping and analysis of Internet projects that discuss the concepts above referred and contribute for the reconfiguration of the contemporary notion of authorship is accomplished. Among them: AfterSherrieLevine.com/AfterWalkerEvans.com , by Michael Mandiberg, 2001, and Society of the Spectacle (A Digital Remix) by Mark Amerika, Trace Reddell and Rick Silva, 2004. Such an empirical corpus was split into two categories proposed by Eduardo Navas: Selective and Reflexive Remix. The typologies of agency suggested by these works bring up questions such as the production and consumption relations, interactivity, property, control and micropolitics, as well as pointing towards the definition of both to the very own aesthetics and politics of the intercrossing between network culture and remix culture